The Overall Anxiety Severity and Impairment Scale as an Outcome Measure in Internet-Delivered Cognitive Behavioral Therapy for Anxiety Disorders: Observational Study - Boris Karpov; Jari Olavi Lipsanen; Ville Ritola; Tom Rosenström; Suoma Saarni; Satu Pihlaja; Jan-Henry Stenberg; Paula Laizane; Grigori Joffe (JMIR Publications, 2023)
BackgroundInternet-delivered cognitive behavioral therapy (iCBT) is effective in the treatment of anxiety disorders. iCBT clinical trials use relatively long and time-consuming disorder-specific rather than transdiagnostic anxiety measurements. Overall Anxiety Severity and Impairment Scale (OASIS) is a brief self-report scale that could offer a universal, easy-to-use anxiety measurement option in disorder-specific and transdiagnostic iCBT programs. ObjectiveWe aimed to investigate relationships between OASIS and disorder-specific instruments in iCBT. We expected these relationships to be positive. MethodsWe investigated patients in original nationwide iCBT programs for generalized anxiety disorder (GAD), obsessive-compulsive disorder, panic disorder, and social anxiety disorder, which were administered by Helsinki University Hospital, Finland. In each program, anxiety symptoms were measured using both disorder-specific scales (the 7-item Generalized Anxiety Disorder scale, Penn State Worry Questionnaire, revised Obsessive-Compulsive Inventory, Panic Disorder Severity Scale, and Social Phobia Inventory) and by OASIS. A general linear model for repeated measures (mixed models) and interaction analysis were used for investigating the changes and relationships in the mean scores of OASIS and disorder-specific scales from the first session to the last one. ResultsThe main effect of linear mixed models indicated a distinct positive association between OASIS and disorder-specific scale scores. Interaction analysis demonstrated relatively stable associations between OASIS and the revised Obsessive-Compulsive Inventory (F822.9=0.09; 95% CI 0.090-0.277; P=.32), and OASIS and the Panic Disorder Severity Scale (F596.6=-0.02; 95% CI -0.108 to -0.065; P=.63) from first the session to the last one, while the 7-item Generalized Anxiety Disorder scale (F4345.8=-0.06; 95% CI -0.109 to -0.017; P=.007), Penn State Worry Questionnaire (F4270.8=-0.52; 95% CI -0.620 to -0.437; P<.001), and Social Phobia Inventory (F862.1=-0.39; 95% CI -0.596 to -0.187; P<.001) interrelated with OASIS more strongly at the last session than at the first one. ConclusionsOASIS demonstrates clear and relatively stable associations with disorder-specific symptom measures. Thus, OASIS might serve as an outcome measurement instrument for disorder-specific and plausibly transdiagnostic iCBT programs for anxiety disorders in regular clinical practice.